The impact of systematic assessment for adverse events on unscheduled hospital utilization in patients receiving neoadjuvant or adjuvant chemotherapy: A retrospective multicenter study. (9th December 2021) - Kim, Jwa Hoon; Seo, Seyoung; Kim, Jee Hyun; Koh, Su‐Jin; Ahn, Yongchel; Jung, Kyung Hae; Ahn, Jin‐Hee; Kim, Sung‐Bae; Kim, Tae Won; Hong, Yong Sang; Kim, Sun Young; Kim, Jeong Eun; et al.
Abstract: Background: This study was conducted to compare the reported adverse event (AE) profiles and unexpected use of medical services during chemotherapy between before and after the healthcare reimbursement of AE evaluation in patients with cancer. Patients and Methods: Using the electronic medical record database system, extracted patients with breast, lung, gastric, and colorectal cancers receiving neoadjuvant or adjuvant chemotherapy between September 2013 and December 2016 at four centers in Korea were matched using the 1:1 greedy method: pre‐reimbursement group ( n = 1084) and post‐reimbursement group ( n = 1084). Unexpected outpatient department (OPD), emergency room (ER) visit, hospitalization rates, and chemotherapy completion rates were compared between the groups. Results: The baseline characteristics were well‐balanced between the groups. By chemotherapy cycle, hospitalization (1.8% vs. 2.3%; p = 0.039), and ER visit rates (3.3% vs. 3.9%; p = 0.064) were lower in the post‐reimbursement group than that in the pre‐reimbursement group. In particular, since cycle 2, ER visit and hospitalization rates were significantly lower in the post‐reimbursement group than those in the pre‐reimbursement group (2.6% vs. 3.3%; p = 0.020 and 1.4% vs. 2.0%; p = 0.007, respectively), although no significant differences were observed during cycle 1. The OPD visit rates were similar between both groups, regardless of cycles. The post‐reimbursement group had a higher proportion of patients who completed chemotherapy as planned than the pre‐reimbursement group (93.5% vs. 90.1%; p = 0.006). Post‐reimbursement group had more AEs reported, including alopecia, fatigue, diarrhea, anorexia, and peripheral neuropathy, during cycle 1 than the pre‐reimbursement group, which significantly decreased after cycle 2. Conclusion: The introduction of healthcare reimbursement for AE evaluation may help physicians capture and appropriately manage AEs, consequently, decreasing hospital utilization and increasing chemotherapy completion rates. Abstract : Physicians frequently underreport or underestimate the incidence and severity of adverse events (AEs) experienced by patients even in clinical trials and real‐world routine clinical practice. AE profiles and unexpected use of medical services during chemotherapy were compared between before and after the approval of the healthcare policy for the reimbursement of AE evaluation in patients with cancer. The introduction of healthcare reimbursement for AE evaluation may help physicians capture and appropriately manage AEs, consequently, decreasing hospital utilization and increasing chemotherapy completion rates.